Preoperative albumin/globulin ratio has predictive value for patients with laryngeal squamous cell carcinoma - Chen, Wan-Zhi (Oncotarget, 2017)
This study evaluated the predictive value of the preoperative albumin/globulin ratio (AGR) in laryngeal squamous cell carcinoma (LSCC) retrospectively, which has not been reported before. The current study enrolled 241 newly diagnosed LSCC patients in the Second Affiliated Hospital of Nanchang University between January 2005 and December 2010. The optimal AGR cut-off value for overall survival (OS) was determined to be 1.28. Univariate survival analysis identified sex, low AGR, T classification, histological grade and nodal metastasis as factors associated with poor OS. Additionally, a low AGR, T classification, nodal metastasis, and histological grade were associated with poor disease-free survival (DFS) in LSCC patients. In multivariate survival analysis, nodal metastasis and a low AGR remained significant for OS and DFS. Our preliminary study revealed that low preoperative AGR could serve as a valuable and easily-assessed blood-based indicator to predict the prognosis of LSCC patients.